Hubungan Dukungan Sosial Dengan Self Acceptance Pada Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisa - Suandika, Made Suandika; Hidayat, Wiwit Arif; Siwi, Adiratna Sekar (Citra Delima Scientific journal of Citra Internasional Institute, 2024)
Regardless of physical status, CKD patients need to feel self-acceptance towards themselves. In this study, CKD patients undergoing hemodialysis at RSU Dadi Keluarga Purwokerto will be examined for the relationship between social support and self-acceptance. With a cross-sectional approach, non-probability Accidental Sampling as a sample collection strategy, and the G-power software formula for sampling, this research method uses correlative analysis to collect data from 70 respondents. The Unconditional Self-Acceptance Questionnaire (USAQ) and the Social Support Questionnaire were used in this study. 43 respondents (61.4%) were male and aged between 46 and 65 years were the characteristics of the majority. 13 to 24 months are spent on hemodialysis. 18 respondents (25.7%), whose last education was high school or middle school, respectively 49 respondents (70%) and 35 respondents (50%) had jobs. Based on the results of the independent and dependent variables, good social support was obtained for 51 respondents (72.9%) and moderate self-acceptance for 47 respondents (67.1%). With a p-value of 0.000 (p-value 0.005) and a correlation coefficient of 0.619, the findings of this study indicate a substantial relationship between social support and self-acceptance. This relationship is strong. As a result, in someone who has undergone hemodialysis therapy, social support is closely related to self-acceptance.